2008
DOI: 10.1111/j.1365-2443.2008.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

GDNF‐mediated signaling via RET tyrosine 1062 is essential for maintenance of spermatogonial stem cells

Abstract: Well‐organized spermatogenesis, including the maintenance of spermatogonial stem cells (SSCs), is indispensable for continuous male fertility. Signaling by glial cell line‐derived neurotrophic factor (GDNF) via the RET/GDNF family receptor α1 (GFRα1) receptor complex is essential for self‐renewal of murine SSCs and may also regulate their differentiation. When phosphorylated, tyrosine 1062 in RET presents a binding site for the phosphotyrosine‐binding domains of several adaptor and effector proteins that are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Ret also acts through these pathways to promote SSC survival and proliferation (2,38). Ret inactivation results in severe defects in SSC proliferation and differentiation by P7, eventually leading to SSC depletion (8,41). The similarity of the Ret and Foxo phenotypes and these previous studies together strongly argue that Ret downregulation accounts for the observed Foxo phenotypes in SSC maintenance.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Ret also acts through these pathways to promote SSC survival and proliferation (2,38). Ret inactivation results in severe defects in SSC proliferation and differentiation by P7, eventually leading to SSC depletion (8,41). The similarity of the Ret and Foxo phenotypes and these previous studies together strongly argue that Ret downregulation accounts for the observed Foxo phenotypes in SSC maintenance.…”
Section: Discussionmentioning
confidence: 47%
“…These findings strongly argue that the PI3K pathway regulates Ret expression in SSCs and, furthermore, that this regulation occurs via the Foxos. Given the requirement for Ret in SSC maintenance (Ret loss-of-function mutations result in germ cell depletion in mice), the control of Ret by the PI3K pathway via Foxo1 rationalizes the SSC self-renewal phenotype observed in our Foxo mutants (41).…”
Section: Essential Role Of Foxo1 In Ssc Self-renewal and Differentiatmentioning
confidence: 99%
“…Our group and others have demonstrated that glial cellderived neurotrophic factor (GDNF) is the most essential factor for SSC self-renewal and maintenance in rodents [12][13][14][15][16][17][18] and that GDNF signals via binding to its membrane receptor complex containing GFRA1 and RET, both expressed by the spermatogonial stem/progenitor cells [19][20][21][22]. Recent studies have suggested that GDNF signals via multiple pathways to promote the proliferation and self-renewal of SSCs [23][24][25][26][27]. Specifically, we have shown that GDNF acts through the RAS/ MAPK1/2 pathway, stimulating the phosphorylation of RET tyrosine kinase and finally inducing the transcription of the immediate early gene Fos as well as cyclin A and CDK2 protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…3). Studies in RET Y1062F knockin mice suggest that GDNF-RET signaling is essential for the self-renewal of SSCs via tyrosine 1062 (Jijiwa et al 2008).…”
Section: Gdnf Signalingmentioning
confidence: 99%